Remote Control of a Mobile Robot for Inspection and Engineering Work in Ductwork - Jarosław PANASIUK; Waldemar ŚMIETAŃSKI; Michał SIWEK; Piotr PRUSACZYK (Problemy Mechatroniki, 2019)
Inspection and engineering work inside ducts are a serious challenge in terms of logistics and processing. Processing-wise, a major obstacle is the remote control over a modular mobile unit with a variable cinematic configuration and intended to manage complex operating processes. This paper presents the results of the development of a mobile robot for inspection and engineering work. The items of a specific focus of the development work were the remote-control system structure and the control algorithms for the propulsion module control and the operating module control.